The Belief-Desire-Intention Architecture of Sincere Software Agent Environment - Jaafar N.H.; Ahmad A.; Ahmad M.S.; Hamid N.H.A. (UIKTEN - Association for Information Communication Technology Education and Science, 2023)
Software agent is autonomous technology that helps a lot the human being in performing the task. The capability of agent to take actions on behalf of human is one of the reasons why researchers or developers of autonomous systems adapt the human characteristics either in the form of physical or behaviours. Sincerity is one of ethical human behaviour that can be instilled in software agent environment system. To instil the ethical behaviour such as sincerity, the belief-desire-intention (BDI) architecture should be designed. This paper explains the BDI architecture for sincere software agent environment system during performing task 2021. Nur Huda Jaafar et al; published by UIKTEN. This work is licensed under the Creative Commons Attribution-NonCommercial-NoDeris 4.0 License